A Bet on Interdisciplinarity (2014)
After a series of workshops and research carried out by the team of EAFIT Children's University and some researchers, it was evidenced that the development of the workshops constitutes a dialogue of knowledge between different actors (children, workshop facilitators, researchers), with the aim of co -produce multiple answers to a question.